The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fimmu.2020.00690
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Roles of Polysaccharide Capsules in the Intestine

Abstract: The interplay between the immune system and the microbiota in the human intestine dictates states of health vs. disease. Polysaccharide capsules are critical elements of bacteria that protect bacteria against environmental and host factors, including the host immune system. This review summarizes the mechanisms by which polysaccharide capsules from commensal and pathogenic bacteria in the gut microbiota modulate the innate and adaptive immune systems in the intestine. A deeper understanding of the roles of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…As a result, it was thought that polysaccharide vaccines such as PPV23 could activate humoral immunity only, and the cells responsible for humoral immunity are B cells [ 7 ]. To our surprise, the GO terms and KEGG pathways analysis results in this study found several items related to T cells, and this result was similar to several studies reported in recent years [ 44 , 45 ]. With the study of the biological function and immunomodulatory effect of bacterial polysaccharide, more and more of the literature has reported that CPS can activate the T cell population; promote the development of T cells, DCs, or other immune cells; and enhance the functions of immune cells and promote their maturation [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…As a result, it was thought that polysaccharide vaccines such as PPV23 could activate humoral immunity only, and the cells responsible for humoral immunity are B cells [ 7 ]. To our surprise, the GO terms and KEGG pathways analysis results in this study found several items related to T cells, and this result was similar to several studies reported in recent years [ 44 , 45 ]. With the study of the biological function and immunomodulatory effect of bacterial polysaccharide, more and more of the literature has reported that CPS can activate the T cell population; promote the development of T cells, DCs, or other immune cells; and enhance the functions of immune cells and promote their maturation [ 7 , 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that the presence of polysaccharide macromolecules in traditional Chinese medicine tonics cannot be ignored. The beneficial regulation of gut microbiota has been widely reported for polysaccharides, including providing energy for intestinal microorganisms, shaping the diversity of the gut microbiota, protecting bacteria from environmental, and host factors, including the host immune system, and so on ( Porter and Martens, 2017 ; Hsieh and Allen, 2020 ; Sun et al, 2021b ; Song et al, 2021 ). Thus, the polysaccharide in ZXBZ may be separated and tested further for understanding its pharmacological substances.…”
Section: Discussionmentioning
confidence: 99%
“…EPS produced by Bacillus subtilis protects mice from the intestinal pathogen Citrobacter rodentium , which causes acute colitis. It has the ability to block T cell activation in a wide sense, allowing it to regulate T cell-mediated immune responses in a variety of inflammatory disorders [ 65 ]. EPS of Lactobacillus helveticus act as a potential immunomodulatory agent by exhibiting strong effect on elevating the proliferation of macrophages and enhancing phagocytosis, acid phosphatase activity, nitric oxide production and cytokines production [ 66 ].…”
Section: Biological Activities Of Bacterial Epssmentioning
confidence: 99%